Methylomic change in TET1 and TET2 promoters is increased in children with acute lymphocytic leukemia - Refaai, Rofaida; Ragab, Dina; Guirgis, Adel A.; Khalil, Hany (BOHR Journal of Cancer Research, 2023)
Objective: Methylomic changes have been recognized as essential contributors to the development of acute lymphocytic leukemia (ALL). While ALL has traditionally been considered a genetic disease, the increasing importance of epigenetic alterations in leukemogenesis has become evident. Here, our goal was to investigate the changes of DNA methylation level in ALL. Methods: To assess the DNA methylation pattern in ALL, we quantified gene expression of the methylation-related factors, including DNMTs, methionine synthase (MS), and the demethylation factors, TET gene family using qRT[1]PCR. Results: The expression pattern of DNMTs, including DNMT1, DNMT3a, and DNMT3b, was markedly upregulated in samples derived from patients. On the contrary, the expression of the methyl creator, methionine synthase (MTR gene) was down-regulated in samples derived from children with ALL which revealed low concentration of vitamin B12 in their samples. The reduced expression of MTR in children with ALL reveals the disturbance of homocysteine and DNA methylation. Moreover, we examined the expression patterns of TET1, TET2, and TET3 genes implicated in the demethylation process. We found an evident decreasing level of TET1 and TET2 expression in ALL that may refer to an increasing DNA methylation activity in the promoter of the TET gene family. Conclusion: These data suggest the possible alteration in methyaltion-related factors due to methylomic changes within the promoter of TET1 and TET2 genes.